Charakterystyka procesu globalizacji jako czynnika wywołującego zmiany w funkcjonowaniu przedsiębiorstw - Krzos, Grzegorz (Characteristics of globalization as an element generating modification of functioning of companies., 2005)
Globalization is the process of formation, consolidation and accumulation ot the world-wide market. The process gives rise to the unification of the economic and public world and induces the need for a transformation of the economy. This process is unavoidable and is caused by limited home demand, the economy growth in other places of the world, an improvement of technology and the wish to gain more profits. It results in the geographical expansion, diffusion of branches, dispensation of phases, economic integration, standardization of actions, processes, styles and structures. Thanks to the information revolution the signification of time and space has decreased and efficiency has increased. A lot of companies have to learn constantly, search new solutions and innovations, correct communication, make dynamic teams, make quality standards better. These actions can bring to success in global reality.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 115-122